THE ROLE OF CLINICAL PATHWAY IN IMPROVING HOSPITALS COST EFFICIENCY - Taufiqurrahman Taufiqurrahman; Mardiati Nadjib (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Clinical Pathway (CP) is a method of clinical documentation that reflects clinical practice standards for physicians, nurses and other members of healthcare team. Clinical pathways are collaborative guidelines for treating patients focused on diagnosis, clinical problems and stages of care. The advantage is any intervention given and the development of the patient recorded systematically based on the time criteria set and is expected to improve the quality of service and to lower hospital costs. The aim of this narrative review is to assess the role of CP in improving the efficiency of hospital costs. Methods: Narrative review was performed by analyzing the scientific articles obtained through Electronic Library provided by the University of Indonesia through online database list and chooses Science Direct as a search. The keywords used in the search were